Supraglacial microbes use young carbon and not aged cryoconite carbon. (April 2018) - McCrimmon, Drake O.; Bizimis, Michael; Holland, Alexandra; Ziolkowski, Lori A.
Highlights: Microbes on two Alaskan glaciers consume atmospheric carbon dioxide. 90% of cryoconite carbon was not living microbes; it was mineral-bound and aged. Carbon in a cryoconite hole consists of at least two distinct carbon pools. Abstract: Cryoconite holes are depressions in glacial ice surfaces filled with dark debris that reduce albedo. The relative contributions of combustion and microbial carbon to cryoconite carbon are currently not known. To constrain cryoconite organic carbon composition and carbon sources to microorganisms living on glacier surfaces, measurements of bulk organic carbon and microbial phospholipid fatty acids (PLFAs) from supraglacial cryoconite sediment within the ablation zones of Spencer and Matanuska glaciers in southern Alaska were coupled with radiocarbon ( 14 C) analyses. The 14 C content of bulk cryoconite organic carbon on both glaciers was depleted relative to the modern atmosphere, while the PLFAs contained carbon that was recently in equilibrium with the atmosphere. Because the bulk cryoconite material is isotopically distinct from the PLFAs, these results indicate that cryoconite organic carbon is not bioavailable to the microbes. Instead, modern carbon in the microbes suggests that carbon is being quickly cycled by them within the cryoconite. Biomarker and stable isotope analyses of cryoconite organic carbon points to fresh carbon inputs to cryoconite and indicates that combusted fossil carbon is a not a major component of cryoconite organic carbon. Trace element analyses of the bulk cryoconite show crustal inputs and no evidence for excess metals associated with recent combustions sources, indicating that the aged bulk cryoconite organic carbon is likely of rock origin (e.g., shale). This study highlights that microbes in cryoconite holes on these glaciers are fixing atmospheric carbon and not using the aged carbon surrounding them.